Women s voices, feminist visions :classic and contemporary readings /Susan M Shaw, Janet Lee. - Shaw, Susan M.,1960-
An introductory women s studies reader which offers various classic, conceptual, and experiential writings. It contains chapter introductions which provide background information on topics, including explanations of key concepts and ideas and references to the subsequent reading selections